Children's Literacy Activities as a Realization of the School Library Revitalization Program at SDN 1 Moyoketen, Tulungagung Regency - Srirahayu, Dyah Puspitasari; Anugrah, Esti Putri (Tik Ilmeu : Jurnal Ilmu Perpustakaan dan Informasi, 2023)
Currently, the use of devices in children is increasing, accompanied by a decrease in literacy rates. From the results of the study, the level of literacy in children is quite low. To increase interest in reading in children not only requires the role of parents, but the place where they go to school also takes an important role in improving children's literacy. Low literacy of children can be overcome by carrying out various activities regarding literacy itself. Another alternative that can be done is to hold a literacy program in the school library. It aims to assist children in improving and growing their reading literacy as well as the realization of revitalization. This activity took place from July to August at SDN 1 Moyoketen. With the literacy program and library revitalization, it is hoped that it can make students more interested in visiting the library and reading the collections contained in the school library